PENGARUH PEMEREKAN KOTA “ENJOY JAKARTA” TERHADAP CITRA KOTA - Chandra Wibowo Widhianto; Henilia Yulita (Universitas Bunda Mulia, 2016)
Jakarta, as the capital of the Republic of Indonesia, finally for the first time launched the